Development of a differential multiplex real-time PCR assay for porcine circovirus type 2 (PCV2) genotypes PCV2a, PCV2b and PCV2d - Wang, Yin (J Virol Methods, 2020)
A multiplex quantitative real-time polymerase chain reaction (mqPCR) assay was developed and validated for detection and differentiation of porcine circovirus type 2 (PCV2) genotypes, PCV2a, PCV2b and PCV2d. Single nucleotide polymorphism in primers or probes was deployed for different genotype detections, while conserved sequence in the 3' end of a primer and in the middle of a probe was used for the targeted genotype. In silico analysis of 2601 PCV2 ORF2 sequences showed that the predicted strain coverage of the assay was 93.4 % (409/438) for PCV2a, 95.1 % (1161/1221) for PCV2b and 93.6 % (882/942) for PCV2d strains. The PCR amplification efficiencies were 94.5 %, 100.2 %, and 99.2 % for PCV2a, PCV2b and PCV2d, respectively, with correlation coefficients >0.995 for all genotypes. The limits of detection (LOD) were 1.58 × 10(−4) TCID50/mL for PCV2a, 5.62 × 10(−4) TCID50/mL for PCV2b, and 3.16 × 10(−3) TCID50/mL for PCV2d. Sanger sequencing of 74 randomly selected PCV2 positive clinical samples confirmed the genotypes of strains identified by the mqPCR. Validation with clinical samples co-positive for target and non-target pathogens demonstrated that the mqPCR assay specifically detected targeted viruses without cross reacting to each other or to other common porcine viruses.